Attend conferences for professional, personal development. Issue 4 (16th July 2020) - Hodges, Dawn Z.
Abstract : One of my favorite parts of my career was attending state, regional, and national conferences. I set out to gain at least one benefit from every conference I attended, and I always learned something or met someone that added value to my job.